O034 Whole genome sequencing to predict Neisseria gonorrhoeae antibiotic susceptibility: toward tailored antimicrobial therapy. (30th June 2016) - Phillips, Laura; Witney, Adam; Laing, Ken; Gould, Kate; Pond, Marcus; Hall, Catherine; Harding-Esch, Emma; Butcher, Philip; Tariq Sadiq, S
Abstract : Background/introduction: Absence of genotypic resistance-associated markers in Neisseria gonorrhoeae (NG) may predict antibiotic phenotypic susceptibility (APS). NG Whole genome sequencing (NG-WGS) on nucleic acid amplification test (NAAT) positive samples may allow for the avoidance and preservation of first line treatments such as ceftriaxone. However, NG-WGS predictive accuracy for APS should first be established. Aim(s)/objectives: To evaluate NG-WGS "wild-type" predictive value for tetracycline, ciprofloxacin and azithromycin APS. Methods: NG-WGS was performed on prospectively collected NG isolates from a London clinic in 2013, using Illumina MiSeq. Presence of 31 known single nucleotide polymorphisms (SNPs) and other resistance markers for tetracycline, ciprofloxacin, and azithromycin, were compared against a wild-type reference NG strain (FA1090). Results: Of 57 samples, APS to tetracycline, ciprofloxacin, and azithromycin was 14%, 72% and 87% respectively. Genotypic susceptibility ( GeSu ) was defined as absence of SNPs and other resistance-associated markers. For tetracyclines, ciprofloxacin and azithromycin, GeSu-Tet, GeSu-Cip and GeSu-Azi, accurately predicted APS in 7/8 (87.5%; 95% CI 52.9%–97.8%), 40/41 (97.6%; 95% CI 87.4%–99.6%) and 25/25 (100%; 95% CI 86.7%–100%) respectively. One phenotypically resistant GeSu-Tet isolate had "Intermediate" resistance. Of seven isolates, both genotypically and phenotypically susceptible to tetracyclines, all were also susceptible to ciprofloxacin, 24/25 isolates susceptible to azithromycin were also susceptible to ciprofloxacin. Discussion/conclusion: NG-WGS accurately predicted ciprofloxacin and azithromycin but not tetracycline APS. If validated on NG NAAT positive samples, this may allow for new precision ceftriaxone-sparing or ceftriaxone-adjunctive treatment combinations, for a substantial proportion of patients.